D’une conception informée par des données à la généralisation des systèmes cyber-physiques - Philippe Marin (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
The increasing usage of digital technology marks our period and transforms the way we perceive the world. New operative modalities upset the design, the creation and the fabrication processes. Considering the digital technology and the architecture field, we try to identify the recent development and specially the hybridisation between digital and physical realities. We note the changeover from a design to a meta-design activity and the transdisciplinary prominent role. We retain two main activities, one involving data during the design process, the other focusing on cyber-physical systems. We search the features of a “general ecology” which redefine the relations between nature and technic, and the linkage between human and non-human agents.